2022
DOI: 10.2217/imt-2021-0325
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Allergen Immunotherapy Supporting its Disease-Modifying Effect

Abstract: Allergen immunotherapy (AIT) is considered the only disease-modifying treatment available at present for allergic disorders. Its main benefits include improvement of symptoms, decreased need for pharmacotherapy, prevention of new sensitizations and sustained effect after AIT completion. The key pillars of AIT-induced tolerance include a shift from Th2 to Th1 response, an increase of regulatory T and B cells, pro-inflammatory effector cell downregulation and IgE suppression, in addition to IgG4, IgA and IgD ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…We have reported that the effects of allergen-specific immunotherapy meet this description [12]. In addition, based on the initial promising data for biologicals, we assessed this treatment as a disease-modifying therapy [11,13]. The current findings offer further support for the ability of biologics to lead to remission.…”
Section: Discussionmentioning
confidence: 84%
“…We have reported that the effects of allergen-specific immunotherapy meet this description [12]. In addition, based on the initial promising data for biologicals, we assessed this treatment as a disease-modifying therapy [11,13]. The current findings offer further support for the ability of biologics to lead to remission.…”
Section: Discussionmentioning
confidence: 84%
“…They may also prevent mast cell and basophil activation and induce B cells, which secret these blocking antibodies and are responsible for long‐term immunotolerance 10,91–93 . Further cellular responses involve reduced eosinophil recruitment, suppression of Th2 cells, and induction of regulatory cell populations (from innate lymphoid cells, dendritic cells, T and B cells) and regulatory cytokine responses (IL‐10 and TGF‐β), re‐establishing Th1‐Th2 balance 10,41,49,52,87,92,94–96 . More insights into these mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous formulation from Geer Laboratories: 5,000 AU/mL weekly) Marogna et al 74 Th1-Th2 balance. 10,41,49,52,87,92,[94][95][96] More insights into these mechanisms (e.g. role of T cell exhaustion, 92 T follicular regulatory cells, and their epigenetic effects 97 ) are awaited in a preventive clinical setting.…”
mentioning
confidence: 99%
“…Allergen immunotherapy (AIT) is the only disease-modifying treatment available for allergic disorders [69]. Although AIT has been used to treat many atopic diseases, its precise mechanism of action remains unclear [70].…”
Section: Mechanism Of Aitmentioning
confidence: 99%